Prelimimary research on tolerance mechanisms of rice mutant to soil Hg stress - ZENG Bin; ZHAO Li; ZHU Cheng; SUN Zong-xiu (浙江大学学报. 农业与生命科学版)
A pot experiment was conducted to investigate the difference between wild type (Oryza sativa L. subsp. Japonica, cv. Zhonghua 11) and a Hg2+-tolerant mutant in Hg tolerance mechanisms by comparing the growth, yield, Hg2+ concentration, chlorophyll content, net photosynthesis rate, MDA content, activities of major antioxidant enzymes. The results indicated that the mutant was more tolerant to Hg2+. The growth and yield of wild type was more inhibited than those of the mutant. With increasing concentration of Hg2+, the chlorophyll content, net photosynthesis rate decreased more rapidly in wild type. Hg2+ induced more O2 generation and more H2O2 accumulation in wild type compared with mutant. Thus, wild type had higher level of lipid peroxidation. The activities of SOD, CAT in leaves of wild type and the mutant increased under lower Hg2+ concentration, but decreased under higher Hg2+ level. G-POD activity of the mutant and APX activity of wild type both increased with increasing Hg2+ level. The activities of antioxidant enzymes were more inhibited in wild type than those in the mutant. It can be concluded that higher tolerance of the mutant to oxidative stress plays an important role when the plants are exposed to Hg2+ stress.